The associations between maternal and fetal exposure to endocrine-disrupting chemicals and asymmetric fetal growth restriction: a prospective cohort study - Hong, Subeen; Kang, Byung Soo; Kim, Oyoung; Won, Sangeun; Kim, Hyeon Soo; Wie, Jeong Ha; Shin, Jae Eun; Choi, Sae Kyung; Jo, Yun Sung; Kim, Yeon Hee; Yang, Mihi; Kang, Huiwon; et al. (Frontiers in Public Health, 2024)
Recent evidence has revealed associations between endocrine-disrupting chemicals (EDCs) and placental insufficiency due to altered placental growth, syncytialization, and trophoblast invasion. However, no epidemiologic study has reported associations between exposure to EDCs and asymmetric fetal growth restriction (FGR) caused by placenta insufficiency. The aim of this study was to evaluate the association between EDC exposure and asymmetric FGR. This was a prospective cohort study including women admitted for delivery to the Maternal Fetal Center at Seoul St. Mary’s Hospital between October 2021 and October 2022. Maternal urine and cord blood samples were collected, and the levels of bisphenol-A (BPA), monoethyl phthalates, and perfluorooctanoic acid in each specimen were analyzed. We investigated linear and non-linear associations between the levels of EDCs and fetal growth parameters, including the head circumference (HC)/abdominal circumference (AC) ratio as an asymmetric parameter. The levels of EDCs were compared between fetuses with and without asymmetric FGR. Of the EDCs, only the fetal levels of BPA showed a linear association with the HC/AC ratio after adjusting for confounding variables (β = 0.003, p < 0.05). When comparing the normal growth and asymmetric FGR groups, the asymmetric FGR group showed significantly higher maternal and fetal BPA levels compared to the normal growth group (maternal urine BPA, 3.99 μg/g creatinine vs. 1.71 μg/g creatinine [p < 0.05]; cord blood BPA, 1.96 μg/L vs. −0.86 μg/L [p < 0.05]). In conclusion, fetal exposure levels of BPA show linear associations with asymmetric fetal growth patterns. High maternal and fetal exposure to BPA might be associated with asymmetric FGR.